Assessment of nurses’ knowledge and practice regarding the use of transillumination device for establishing venous access - Rubina NesalinRose. T.MSc, Ms.; Nashi Masnad Al Reshidi PhD, Dr.; Rana Mohammad Al Aseeri MSc, Ms. (International Journal of Advanced Nursing Studies, 2019)
Background: Peripheral venous access is frequently performed in various health care settings. However, babiesâ€™ veins are smaller and poorly supported by surrounding soft tissue casing further difficulty of insertion compared to adult patientsâ€™vein. Transillumination device is recommended for difficult insertion of peripheral veins. Nursing practice should accommodate with evolving health care advancement, and therefore the nursesâ€™ are required to develop their knowledge and attitude towards new skill and practice. Objectives: To assess the level of nursesâ€™ knowledge and practice regarding the use of transillumination device for establishing venous access. Methods: A descriptive study design that was conducted among a sample of 20 Nurses working at Hail General Hospital, KSA. The study tool included a questionnaire sheet of 2 parts as demographic variables and then knowledge and practice regarding use of transillumination device for establishing venous access. Selected nurses were asked to fill up the questionnaire sheet. Results: The majority 50% of the nurses were under the age group of 31yrs and above. Most of the 95% nurses were bachelorâ€™s degree and only 5% was masterâ€™s degree. The year of experience were majority of nurses 35% had 7-9 yrs. Designation of nurses indicates, almost 50% of the nurses were working as a Charge Nurse, among 45% as staff Nurse and only 5% as Head Nurse.Obviously, 100% of the nurses perform cannulation in first attempt. Before, 65% of the nurses had no awareness of using veinlite. 100% of the nurses used 26G size cannula.Furtherly, 85% assures that they could incorporate transillumination device into practice. The opinion of 65% nurses feel, this device was easy to use. Conclusion: The study says that, most of the 65% NICU nurses has only average and 35% has good knowledge and practice regarding use of transillumination device for establishing venous access. The nurses have interest in practicing transillumination device and seems to be time saving and effective. Suitable interventional packages need to be given periodically for the effectiveness of qualitative nursing service. Â Â